The Kingdom of Swaziland : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2008)
The Swazi economy has continued to register sluggish economic activity even as rising Southern African Customs Union revenue contributed to a large fiscal surplus and accumulation of international reserves. The unchecked growth of insufficiently regulated saving and credit cooperatives poses risks to the financial system. Fiscal policy should safeguard priority spending and fiscal sustainability. Executive Directors commend the government's effort in rebuilding international reserves. Further efforts are needed to improve the quality and timeliness of data to better facilitate policy formulation and monitoring.